Analyzing chaotic systems with multi-step methods: Theory and simulations - Meriem Mansouria Belhamiti; Zoubir Dahmani; Jehad Alzabut; D.K. Almutairi; Hasib Khan (Alexandria Engineering Journal)
Identifying and analyzing fixed points plays a crucial role in chaos theory for grasping the system behavior and advancing the understanding of its fundamental mechanics. This study explores new chaotic nonlinear integro-differential systems with four variables, employing Caputo–Fabrizio and Atangana–Baleanu derivatives. We confirm the presence and reliability of solutions and offer a real-life example. Additionally, we implement the suggested multi-step techniques on different nonlinear chaotic systems to demonstrate their accuracy.